Enterprise environment modeling for penetration testing on the OpenStack virtualization platform - Vincent Karovic; Jakub Bartalos; Vincent Karovic; Michal Gregus (Journal of Global Business Insights, 2021)
The article presents the design of a model environment for penetration testing of an organization using virtualization. The need for this model was based on the constantly increasing requirements for the security of information systems, both in legal terms and in accordance with international security standards. The model was created based on a specific team from the unnamed company. The virtual working environment offered the same functions as the physical environment. The virtual working environment was created in OpenStack and tested with a Linux distribution Kali Linux. We demonstrated that the virtual environment is functional and its security testable. Virtualizing the work environment simplified the organization’s security testing, increased resource efficiency, and reduced the total cost of ownership of certain devices.